(3QSGdI Ydi ShQI GdaGJMIs - (3Gdehdj YHO GdcQjes
(3ChdgG (B:s
(3GdMeO ddg GdhgGH CfRd aGJMI GdcJGH CeG HYO abO JbQQ Cf aGJMI GdcJGH Ce GdbQBf hCe GdcJGH dGTJeGdgG Ydi ebGUOg Ydi GdELeGd hcKQJ GdCbGd ai cjajI GdCTJeGd s
(3BNQgG (B:s
(3aHCJ GTJeGd GdShQg Ydi ebGUO GdbQBf ef EQTGO hCfhGY GdEMSGf Edi GdEjeGf hGdcdGe hGdEMSGf GdLGeY deQGJH GdaQbGf heJi YO SejJ Ce GdbQBf JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B26s
(3HgG fXGe GdJYbjHIs
(3YdjgG Jedc HGSe EHQGgje Hf eMeO GdMfai HJGQjN (B1077 (3g` JaSjQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B266) s
Keywords: (3GdeLGejYs